Ratio of Legis Dissolution of Community Organizations Without Due Process Of Law - agung Barok Pratama, agung (UNIB Press, 2024)
This research examines the Authority of the Government in the Dissolution of Community Organizations. The purpose of the research is to find out the ratio legis of the regulation of the dissolution of community organizations without a judicial process and the dissolution of community organizations in a democratic perspective. This research is a type of normative juridical research using prescriptive analysis techniques. The results of this study indicate that the ratio legis of the government dissolving community organizations is an affirmation of the principle of contrarius actus so that the government with its authority can dissolve community organizations without the need to wait and go through the judicial process (due process of law). And the dissolution of community organizations without a judicial process does not reflect a characteristic of a state of law based on democratic principles and ignores the constitutional rights of citizens to guarantee freedom of association, assembly and expression.